Human Resource Management with the HRMS.OBEC information system of the Development and Legal Affairs Office of Personnel Management under the Office of Basic Education Commissio - Petchara, Nonpawit; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (Journal of Dhamma for Life, 2025)
This research aimed to develop and propose a human resource management model using the HRMS.OBEC information system of the Office of Personnel Management and Legal Affairs under the Office of the Basic Education Commission (OBEC). The study identified key components and indicators through expert interviews and conducted exploratory and confirmatory factor analyses with 327 participants, including educational administrators, school directors, and personnel from secondary education service area offices. The findings revealed six major components of the HRMS.OBEC-based human resource management model: (1) data management and security, (2) technological integration to enhance system efficiency, (3) development of comprehensive personnel management functions, (4) analytical and reporting systems for management, (5) information management for analysis and decision-making, and (6) self-service functionalities for personnel. The proposed model was found to be appropriate, feasible, and beneficial for managing human resources in the Thai bureaucratic system. It supports efficient personnel management aligned with digital government policies and modern public administration reform.